Multiple Intelligences as a Pedagogical Activation System in Primary Education - Supaat Supaat; Taufikin Taufikin; Fitria Noor Lailatur Rizqi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
This study aims to reconstruct multiple intelligences as a system for activating human potential in primary education through a multi-site qualitative study in five schools in Kudus, namely MI Negeri Prambatan, SD al-Islam Glantengan, SD Islam Nawakartika Langgardalem, MI Muhammadiyah Damaran, and SD Kristen Cahaya Nur Barongan. The research was conducted from August 2023 to February 2024 and involved five school principals and ten teachers as key informants. Data were collected through in-depth observation, semi-structured interviews, and document analysis, and were then analyzed thematically and constructively to develop theoretical propositions. The findings show that multiple intelligences operate through three systemic mechanisms: the diagnosis of potential through continuous observation, the activation of potential through a multimodal learning ecosystem that integrates various types of intelligence, and the validation of potential through multidimensional, authentic assessment. This process not only increases learning engagement but also transforms students' identities from passive recipients to active agents capable of developing reflective, creative, and adaptive thinking capacities. This research contributes by developing the Multiple Intelligences as Pedagogical Activation System theoretical model, which reconceptualizes the role of multiple intelligences from mere learning strategies into an ontological system for activating human potential, and opens new directions in the development of educational theory and practice that are more oriented towards transforming student potential.